Next-generation biofuels: Survey of emerging technologies and sustainability issues - Zinoviev, Sergey (2010)
Next-generation biofuels, such as cellulosic bioethanol, biomethane from waste, synthetic biofuels obtained via gasification of biomass, biohydrogen, and others, are currently at the center of the attention of technologists and policy makers in search of the more sustainable biofuel of tomorrow. To set realistic targets for future biofuel options, it is important to assess their sustainability according to technical, economical, and environmental measures. With this aim, the review presents a comprehensive overview of the chemistry basis and of the technology related aspects of next generation biofuel production, as well as it addresses related economic issues and environmental implications. Opportunities and limits are discussed in terms of technical applicability of existing and emerging technology options to bio-waste feedstock, and further development forecasts are made based on the existing social-economic and market situation, feedstock potentials, and other global aspects. As the latter ones are concerned, the emphasis is placed on the opportunities and challenges of developing countries in adoption of this new industry.An overview of technical aspects of production technologies for next-generation biofuel is presented. Complemented with their related economical and environmental assessment results, an insight into the sustainability of the technologies, and an analysis of the opportunities and limits of future development, is given. © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.